The Effect of Methanol-Gasoline (M20) and Ethanol-Gasoline (E20) Blends on Material Compatibility - Nurmajid Abdurrojaq; Rizal Zaelani; Belva Adam Haley; Nur Allif Fathurrahman; Riesta Anggarani; Cahyo Setyo Wibowo; Maymuchar Maymuchar (Testing Center for Oil and Gas LEMIGAS, 2022)
Alcohol has the potential to be used as an alternative to fossil fuels to reduce total emissions from spark-ignition (SI) engines. The impact of a mixture of 20% methanol and ethanol in gasoline on the compatibility of Ethylene Propylene Diene Monomer (EPDM) and polyamide materials, which are used as fuel hoses in SI vehicles, is presented in this study. The immersion test methodology was employed to study the influence of both types of alcohol on gasoline blend to compatibility properties i.e., hardness and weight change. Based on the result, EPDM and polyamide materials have different characteristics of material compatibility with E20 and M20. Tests on M20 and E20 fuel samples on EPDM material show a higher effect on hardness by 5-9% than pristine gasoline. Additionally, there was no change in the weight of the polyamide material in the RON 90, E20, and M20 test samples. However, there was a change in the hardness of the polyamide material by 6-11% in RON 90, E20, and M20 fuels. Moreover, there was no change in the FTIR spectrum, indicating that there was no dissolution of the EPDM and polyamide materials into the test fuel for 6 weeks of immersion.